Economic Impact of FMD in cattle and buffaloes in India - GOVINDARAJ G; GANESH KUMAR B; KRISHNAMOHAN A; RAVEENDRA HEGDE; NANDAKUMAR S; KOKILA PRABHAKARAN; VINAY MOHAN; NARESH KAKKER; LOKHANDE T; KRISHNA SHARMA; AMIT KANANI; LIMAYE A; et al. (Indian Journal of Animal Sciences, 2020)
In India, among various diseases that limit livestock production, Foot and Mouth Disease (FMD) stands first and affects thousands of animals every year. The estimation of loss due to FMD is of paramount importance for designing appropriate control plans. The economic impact studies on various livestock diseases including FMD are very minimal and hence this study assessed the economic loss due to FMD in cattle and buffaloes in few states and overall loss in the country. The total loss estimated comprise of milk yield reduction, unavailability of draught power, distress sale, treatment cost, mortality and opportunity cost of labour based on primary survey undertaken in 10 states and one Union territory. The results revealed that there was variation in loss levels between species and among the study states due to variation in disease incidence and severity levels, productive capacity of the animals, animal health infrastructure in the respective states, etc. The total estimated loss due to FMD in cattle and buffalo was INR 20,897 crore during 2013-14 with wide variation in magnitude across the states studied. The study provided empirical evidence of loss due to FMD in cattle and buffaloes in few states and overall loss in the country.